Evaluation of pomegranate rind (Punica granatum) hydroethanolic extract on blood parameters in male mice treated by Irinotecan Hcl - N Mirazi (Armaghane Danesh Bimonthly Journal, 2015)
Background & aim: Irinotecan Hcl is the first order drug for some neoplasm treatment in patients. Irinotecan Hcl has side effects on blood such as anemia and leukopeny. The aim of this study was to evaluate erythropoetic effects of the pomegranate hydroethanolic extract were examined on mice which treated by irinotecan Hcl.